2020
DOI: 10.1088/1361-6668/ab951f
|View full text |Cite
|
Sign up to set email alerts
|

Secondary CLIQ, a robust, redundant, and cost-effective means of protecting high-field accelerator magnets

Abstract: Secondary CLIQ is a quench protection method for protecting high-field accelerator magnets that involves charged capacitors into secondary normal-conducting coils that are magnetically coupled to the superconducting coils. The resulting coupling losses quickly brings the magnet to normal state and safely discharges it. No direct electrical or thermal link is required between the primary and secondary coils, and robust insulation is placed in between them. The two secondary circuits per magnet ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A new quench protection system named Secondary CLIQ (S-CLIQ) was recently proposed [14], which relies on two sets of normal-conducting auxiliary coils that are electrically insulated from the coils to protect, but strongly magnetically coupled to them. The magnet and auxiliary coils are schematically illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new quench protection system named Secondary CLIQ (S-CLIQ) was recently proposed [14], which relies on two sets of normal-conducting auxiliary coils that are electrically insulated from the coils to protect, but strongly magnetically coupled to them. The magnet and auxiliary coils are schematically illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, it was shown that auxiliary coils placed outwards of the magnet coils and corresponding to about 20% of the magnet coils' cross-section were sufficient to effectively protect a 16 T block-coil magnet [14]. In this publication, a S-CLIQ auxiliary coil design to protect a block-coil magnet, with a cross-section of less than 8% of that of the coils to protect, is explored through simulations.…”
Section: Introductionmentioning
confidence: 99%